Concurrent display of both alpha- and beta-turns in a model peptide - Srinivas, Deekonda; Vijayadas, Kuruppanthara N.; Gonnade, Rajesh G.; Phalgune, Usha D.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This article describes a model peptide that concurrently displays both alpha- and beta-turns, as demonstrated by structural investigations using single crystal X-ray crystallography and solution-state NMR studies. The motif reported herein has the potential for the design of novel conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Carbohydrate-derived conformationally restricted bicyclic dipeptides as potential hetero foldamer building blocks - Ramesh, Veera V. E.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Tetrahedron-Asymmetry, 2012)
Starting from carbohydrate precursors, hetero foldamer building blocks featuring diverse amino acid side chains and stereochemistry have been accessed via a multi-step synthetic protocol. These conformationally restricted bicyclic dipeptide building blocks are characterized by a constrained beta-lactam ring fused with a pyrrolidine ring carrying a hydroxyethylamine isostere (HEA) on the backbone. These building blocks offer the possibility of developing foldamers with interesting structural architectures, conspicuously different from those classically observed. Furthermore, such hetero-building blocks have the potential to augment the conformational space available for foldamer design with diverse backbone conformations and structural architectures. (C) 2012 Elsevier Ltd. All rights reserved.

Conformational modulation of Ant-Pro oligomers using chirality alteration of proline residues - Kale, Sangram S.; Kotmale, Amol S.; Dutta, Achintya Kumar; Pal, Sourav; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2012)
Structural modulation of Ant-Pro (anthranilic acid-proline) oligomers has been carried out by chirality alteration of the proline residues. The results suggest that the chirality altered oligomers show well-defined helical conformation featuring nine-membered hydrogen bonding interactions - without compromising conformational rigidity.

Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.

Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Conformational modulation of peptide secondary structures using beta-aminobenzenesulfonic acid - Kale, Sangram S.; Kunjir, Shrikant M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
This communication describes the influence of beta-aminobenzenesulfonic acid ((S)Ant) on the conformational preferences of hetero foldamers. The designed (Aib-(S)Ant-Aib)(n) and (Aib-(S)Ant-Pro)(n) oligomers display a well-defined folded conformation featuring intramolecular mixed hydrogen bonding (7/11) and intra-residual (6/5) H-bonding interactions, respectively.

Conformational modulation of peptides using beta-amino benzenesulfonic acid ((S)Ant) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication describes the utility of a conformationally restricted aromatic beta-amino acid (2-aminobenzenesulfonic acid, (S)Ant) inducing various folding interactions in short peptides. Sandwiching (S)Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.

Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule - Shivakumar, K.I.; Goudappagouda.; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2018)
We report a novel set of easily tailorable C-3 symmetric molecules with a pi-extended core and adorned with different thioalkyl groups, exhibiting solvatofluorochromic and amphoteric redox behaviour. The nearly planar core exhibits intermolecular face-to-face pi-stacking, S...S and intramolecular S...O interactions. Current-sensing atomic force microscopy studies revealed a high conductivity of similar to 0.15 mS cm(-1) in the undoped J-aggregate nanofibres of the thiopropyl appended gelator.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule (vol 54, pg 212, 2018) - Shivakumar, Kilingaru I.; Goudappagouda; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2019)
Correction for `Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule' by Kilingaru I. Shivakumar et al., Chem. Commun., 2018, 54, 212-215.

Carbamate-Protected (BOC and O-NB) 2-Aminopyrimidinedione-based janus G-C nucleobase motifs as building blocks for supramolecular assembly and smart polymers - Singh, Dharmendra; Lakshmi, Durga; Meena, Chhuttan L.; Krishna, Gamidi Rama; Sanjayan, Gangadhar J. (Journal of organic chemistry, 2023)
In this paper, we report ``carbamate protected'' 2-aminopyrimidinedione-based Janus G-C nucleobases (2-APD Janus G-C nucleobases) featuring polymerizable groups and self-complementary triple H-bonding motifs DDA and AAD as building blocks for developing smart polymers and self-healing materials. The carbamate-masked H-bonding motif, cleavable under acidic (BOC group) or photocleavable (O-nitrobenzyl group) conditions, would facilitate the synthesis of smart polymers by alleviating aggregation during polymerization which in turn would exclude self-assembly-assisted solubility issues. Ready accessibility in excellent yields coupled with the possibility for facile introduction of polymerizable groups would make these building blocks excellent candidates for diverse polymerization applications.

Creep resistance in doubly crosslinked dynamic covalent networks - Mondal, Swagata; Wong, Alexander J.; Wagh, Mahendra A.; Alperstein, Lily; Sanjayan, Gangadhar J.; Sumerlin, Brent S. (POLYMER CHEMISTRY, 2024)
Vitrimers are a unique class of thermosets that demonstrate reprocessability and recyclability due to dynamic bond exchange at crosslinking sites. However, the same dynamic bond exchange predisposes vitrimers to macroscopic deformation and creep under constant stress, which limits many practical applications. Herein, we demonstrated that the incorporation of Janus-faced guanine-cytosine diamine (GCBDam) functionality within vinylogous urethane vitrimers leads to significant creep resistance due to network reinforcement via hydrogen bonding. The supramolecular associations of the GCBDam groups retarded stress relaxation at temperatures as high as 160 degrees C. Further, rheological data suggested that the cooperative nature of the bifunctional Janus-faced hydrogen bonding moieties allowed the GCBDam to act as ``stickers'' within the dynamic covalent networks. These results indicate that incorporating the bifunctional supramolecular moiety improved dimensional stability while conserving the hallmark vitrimer property of reprocessability. This work demonstrates that incorporating Janus-faced supramolecular moieties in vinylogous urethane vitrimers improved dimensional stability while conserving the hallmark vitrimer property of reprocessability.